Sri Lanka : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2001)
After weakening in 1999, GDP growth has increased strongly in 2000, led by exports. The savings-investment gap has increased from 1 3/4 percent of GDP in 1998 to 3u percent of GDP in 1999, widening further to 7 percent of GDP in 2000. Agriculture has grown by 4 1\2 percent in 1999, registering a broadly similar growth rate as manufacturing for the first time in many years. In contrast, agricultural output performance was mixed during 2000. Manufacturing has slowed to only 4 1\2 percent in 1999, significantly below the average growth of nearly 8 percent recorded in 1997 and 1998.